Trade related infections: farther, faster, quieter - Arima Yuzo; Kimball Ann; Hodges Jill R (BMC, 2005)
Abstract Modern global trading traffics large volumes of diverse products rapidly to a broad geographic area of the world. When emergent infections enter this system in traded products their transmission is amplified. With truly novel emergent infections with long incubation periods, such as Human Immunodeficiency Virus (HIV) or variant Creutzfeld Jacob Disease (vCJD), this transmission may silently disseminate infection to far distant populations prior to detection. We describe the chronology of two such "stealth infections," vCJD and HIV, and the production, processing, and distribution changes that coincided with their emergence. The concept of "vector products" is introduced. A brief case study of HIV incursion in Japan is presented in illustration. Careful "multisectoral" analysis of such events can suggest ecologically critical pathways of emergence for further research. Such analyses emphasize the urgency of implementing safety measures when pathogens enter globally traded products.